Prognosis and clinical characteristics of patients with 3β-hydroxy-Δ5-C27-steroid dehydrogenase deficiency diagnosed in childhood: A systematic review of the literature. Issue 7 (18th February 2022) - Zhang, Yuan; Yang, Chun-Feng; Wang, Wen-Zhen; Cheng, Yong-Kang; Sheng, Chu-Qiao; Li, Yu-Mei
Abstract: Objectives: 3β-hydroxy-Δ5-C27-steroid dehydrogenase deficiency is a rare autosomal recessive condition. So far fewer than 100 cases have been reported and the factors affecting the prognosis are not yet established. The objective of this study is to explore a possible prediction of the outcome of this rare condition. Methods: This review was undertaken and reported in accordance with the preferred reporting items for systematic review and meta-analyses guidelines. Demographics, clinical features, gene data, treatment strategies and prognoses at the last follow-up were extracted and summarized. Patients were divided into 2 groups (alive with native liver and liver transplantation/died). Risk factors for the different clinical features were identified. Results: 87 patients that were taken from 7 case reports and 9 case series were included. 38 (38/63, 63.0%) of them presented initial symptoms when they were younger than 1 month and 55 (55/63, 87.3%) less than 1 year. There is a larger proportion of patients younger than 1 month or 1 year at the age of symptom onset in the liver transplantation /died group than patients in alive with the native liver group. The majority of patients (53/62, 85.5%) were diagnosed before the age of 5 year. In all cases, 65 (predicted) pathogenic variants have been identified. Over 70% of patients carried an HSD3B7 variant on exon 1, 4, 5 or 6. 71 (81.6%) were alive at the last follow-up, 16 (18.4%) underwent liver transplantation or died. No significance was found between the group alive with native liver and group liver transplantation /died. Conclusion: Age of onset of the symptoms may be a potential factor that determines the outcome of patients with 3β-HSD deficiency, patients presented with symptoms and signs at an age younger than 1 month or even 1 year may have a worse prognosis. Since there is no difference between clinical outcome and zygosity of gene mutation, we recommend a further study about any possible relationship between mutation site and clinical characteristics or prognosis.